What’s Going into the Box? An Inquiry into the Social and Ecological Embeddedness of Large-scale EU and US Box Schemes - Ostrom, Marcia; Kjeldsen, Chris; Kummer, Susanne; Milestad, Rebecka; Schermer, Markus (The International Journal of Sociology of Agriculture and Food, 2018)
Food distribution systems referred to as box schemes have gained a foothold in organic markets across Europe and North America. This model has the potential to scale up direct-marketing strategies by aggregating products from multiple producers and efficiently assembling and delivering them on a regular basis to large networks of consumers. Box scheme organizers generally seek to attract regular customers based on the distinctive attributes and values associated with their products and their unique business model that attempts to build long-term relationships between consumers and farmers. This article explores the organizational dynamics of five large, multi-farm box schemes in relation to their stated values and organizational strategies using cases from Sweden, Denmark, Austria, and the United States.?Different aspects of ecological and social embeddedness are considered and analysed for the five cases based on their stated values and their organizational strategies, including to what degree non-economic values are identified, communicated, and applied throughout the supply chain. The value of geographical proximity is examined with respect to the tension created by consumer demand for variety throughout the seasons and the spatial organization of sourcing and distribution that such a system entails. Additionally, the organizational challenges encountered by box schemes during periods of rapid growth are compared and contrasted with respect to the different organizational strategies employed across the five cases. This article seeks to contribute to the research literature by analysing box schemes as an institutional innovation that can potentially bridge the interests shared by producers and consumers in harnessing market relationships to accomplish larger social and environmental goals.